The effect of probiotic and synbiotic supplementation on appetite-regulating hormones and desire to eat: A systematic review and meta-analysis of clinical trials. (January 2023) - Noormohammadi, Morvarid; Ghorbani, Zeinab; Löber, Ulrike; Mahdavi-Roshan, Marjan; Bartolomaeus, Theda U.P.; Kazemi, Asma; Shoaibinobarian, Nargeskhatoon; Forslund, Sofia K.
Abstract: Recent studies have demonstrated the effect of probiotics, prebiotics, and synbiotics on adiponectin and leptin levels; however, those findings remain contested. The present study aimed to explore the impact of probiotics/synbiotics on appetite-regulating hormones and the desire to eat. Methods: A systematic review was conducted by searching the Medline (PubMed) and Scopus databases from inception to December 2021, using relevant keywords and MeSH terms, and appropriate randomized controlled trials (RCTs) were extracted. The standardized mean differences (SMD) and 95% confidence intervals (95%CIs) were calculated as part of the meta-analysis using a random-effect model to determine the mean effect sizes. Analysis of Galbraith plots and the Cochrane Chi-squared test were conducted to examine heterogeneity. Results: Meta-analysis of data from a total of 26 RCTs (n = 1536) showed a significant decrease in serum/plasma leptin concentration following probiotic/synbiotic supplementation (SMD: −0.38, 95%CI= −0.638, −0.124); P-value= 0.004; I 2 = 69.4%; P heterogeneity < 0.001). The leptin level decrease from probiotic/synbiotic supplementation was higher in patients with NAFLD than those with overweight/obesity or type 2 diabetes mellitus/ metabolic syndrome/ prediabetes. Probiotic/synbiotic supplementation was associated with a trending increase in adiponectin levels, stronger in patients with type 2 diabetes mellitus, metabolic syndrome, and prediabetes (SMD: 0.25, 95%CI= 0.04, 0.46) µg/mL; P-value= 0.021; I 2 = 16.8%; P heterogeneity= 0.30). Additionally, supplementation with probiotic/synbiotic was linked to a slight increase in desire to eat (SMD: 0.34, 95%CI= 0.03, 0.66) P-value = 0.030; I 2 = 39.4%; P heterogeneity= 0.16). Conclusion: Our meta-analysis indicates a favorable impact of probiotic/synbiotic supplementation on regulating leptin and adiponectin secretion. Graphical Abstract: ga1